Proyeksi Kebutuhan Air Bersih Penduduk Di Kelurahan Sri Meranti Dan Kelurahan Umban Sari Kecamatan Rumbai Kota Pekanbaru - Jordi Rifaldi; Jecky Asmura; Aryo Sasmita (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Sri Meranti and Umban Sari are located in Rumbai district Pekanbaru with the vast region of 8,59 km2 and 8,64 km2. The closest area to the city is Sri Meranti with 5 km distance straight. The needs of clean water in Sri Meranti and Umban Sari have served by Tirta Siak Municipal Waterworks Pekanbaru, but it is not serving the amount needed to the development in the services of clean water. The purpose of this research is to estimate and count the needs of clean water in Sri Meranti and Umban Sari in Rumbai district Pekanbaru until 2032. After analyzing the number of residents, obtained the results of the number of people in Sri Meranti and Umban Sari in the district Rumbai Pekanbaru in 2032 is 50.749 people. And the number of water demand is 126,87 l/sec.Keywords: Development, Water Demand, Clean Water